2005
DOI: 10.1097/00001813-200503000-00005
|View full text |Cite
|
Sign up to set email alerts
|

EF24, a novel synthetic curcumin analog, induces apoptosis in cancer cells via a redox-dependent mechanism

Abstract: In this study, we show that the novel synthetic curcumin analog, EF24, induces cell cycle arrest and apoptosis by means of a redox-dependent mechanism in MDA-MB-231 human breast cancer cells and DU-145 human prostate cancer cells. Cell cycle analysis demonstrated that EF24 causes a G2/M arrest in both cell lines, and that this cell cycle arrest is followed by the induction of apoptosis as evidenced by caspase-3 activation, phosphatidylserine externalization and an increased number of cells with a sub-G1 DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
175
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(202 citation statements)
references
References 39 publications
12
175
1
Order By: Relevance
“…2,3 Recently, curcumin has become a focus of interest with regard to its possible antitumor effects in prostate cancer. [12][13][14][15][16][17][18] This study shows for the first time, to our knowledge, that curcumin exerts an inhibitory effect on the invasiveness of DU-145 prostate cancer cells, and confirms this via both in vitro and in vivo testing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…2,3 Recently, curcumin has become a focus of interest with regard to its possible antitumor effects in prostate cancer. [12][13][14][15][16][17][18] This study shows for the first time, to our knowledge, that curcumin exerts an inhibitory effect on the invasiveness of DU-145 prostate cancer cells, and confirms this via both in vitro and in vivo testing.…”
Section: Discussionsupporting
confidence: 78%
“…The results of previous studies have revealed that curcumin exerts pleiotropic effects on prostate cancer cells; however, its functions in invasion and metastasis have yet to be clearly elucidated. [12][13][14][15][16][17][18] Therefore, we assessed the effects of curcumin on the in vitro invasion of prostate cancer cells (DU-145), and further attempted to determine, using a tumor xenograft model, whether curcumin effected an inhibition of prostate cancer cell invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that formation of curcumin-GSH adducts lead to inactivation of parent curcumin's activity. This is, however, unlikely because glutathionylated curcumin has been reported to be more active than curcumin [57]. We also found that NAC reverses the effect of curcumin, most likely by increasing intracellular GSH contents.…”
Section: Discussionmentioning
confidence: 48%
“…Importantly, in animal models EF24 has demonstrated a superior pharmacokinetic and activity profile relative to curcumin while remaining well tolerated. 10,11 In addition, the compound inhibits vascular endothelial growth factor-induced angiogenesis in rabbit and mice models and causes significant reduction in tumor size in human breast cancer xenografts in athymic nude mice. 12 In this study, we set out to elucidate aspects of the molecular mechanism of action of EF24.…”
Section: Introductionmentioning
confidence: 99%